Adhesive properties of graphene oxide and its modification with RGD peptide towards L929 cells. (March 2021) - Jagiełło, Joanna; Kuśmierz, Marcin; Kijeńska-Gawrońska, Ewa; Winkowska-Struzik, Magdalena; Święszkowski, Wojciech; Lipińska, Ludwika
Abstract: Properly prepared substrate for cell culturing is a crucial factor to maintain good viability and proliferation of the cells. Graphene oxide (GO), due to its physicochemical properties, can be easily modified with biomolecules, which enable the interaction with different types of cells. Moreover, highly hydrophilic GO flakes itself can provide good conditions for cell culture. The aim of the study was to determine the adhesion ability of GO towards L929 cells by comparing the morphology and viability with the results obtained for cell culturing on GO modified with the Arg-Gly-Asp (RGD) peptide and standard tissue culture polystyrene well plates. This work presents the routes of efficient modification of GO with RGD molecules. This peptide is present in proteins building chondrocytes, fibroblasts, macrophages, and extra- and intracellular matrices and is responsible for binding the cell integrins. Successful functionalization was conducted with the use of carbodiimide (EDC·HCl) and N -Hydroxysuccinimide (NHS) that activated the GO surface for binding molecules (peptides) with amine groups. Samples were characterized with SEM, Raman, FTIR and XPS spectroscopy. One step functionalization revealed as a very effective method for peptide immobilization on the GO giving ca. 71 μg/cm 2 of RGD attached to the GO surface. On the basis of these studies, the materials for cellular research were selected. Morphology and viability/proliferation of L929 cells incubated on the prepared graphene substrates were investigated. Biocompatibility of each of the tested materials was found on the basis of adhesion and viability tests. GO, because of oxygen functional groups present on its surface, led to a better cellular response in comparison to control glass slides and standard polystyrene well plates, making this material a competitive substrate for cell culturing. The presence of RGD on the GO surface did not affect the viability of L929 cells, which leaded to the conclusion about good adhesive properties of GO towards the cells. Based on the presented work, it can be concluded that GO is a material that can be successfully used for cell culture and can be competitive with standard polystyrene substrate due to the possibility of its modification according to specified needs.